Developing a toolkit to help smaller local authorities establish strong net zero governance in the UK - Gudde, Peter; Bury, Nicolas; Cochrane, Peter; Caldwell, Nicholas (Frontiers in Sustainable Energy Policy, 2024)
The Skidmore Review of UK Government's net zero approach highlights a lack of a national framework which establishes local government role, responsibilities and area-based governance arrangements. Although unified political leadership agreed as part of devolution deals has helped some areas to marshal resources and support, the national delivery landscape for net zero remains patchy. This paper presents a mixed methods research approach focusing on the way that net zero governance is emerging to develop a toolkit to help local areas improve local arrangements. The toolkit incorporates a set of governance models, a method for assessing the values of good governance, a governance improvement process and an illustration of how the toolkit can be employed using three cases where the two-tier public administrative structure applies. The research to derive the toolkit suggests that although change is happening it lacks the coherence and scale needed, with non-urban multiple-tier public administrations getting left behind by their metropolitan, single-tier counterparts creating a credibility and performance gap between political rhetoric and local net zero delivery. This observed inertia highlights the need to change governance processes and practices if public administration is going to deliver its part of net zero effectively outside the UK Metropolitan areas. The gap in support for local government to develop net zero governance arrangements is well recognised in both the research and publicly funded research programmes. In the current financial climate, UK local authorities need simple, effective tools to help them build strong relationships with wider society if the UK is to build locally led transformational change for net zero.